2022
DOI: 10.3389/fpubh.2022.927454
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the self-directed learning approach and attitude on online learning ineffectiveness: The mediating roles of internet cognitive fatigue and flow state

Abstract: Online learning has become an important learning approach in universities. However, since many students may have been exposed to online learning for the first time during this period of the COVID-19 pandemic, the quality factors of online learning and psychological distress of students need to be considered in the research on their learning. This paper discusses factors that influence the learning effect of university students in the online learning environment. A total of 377 university students participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
(73 reference statements)
0
13
0
Order By: Relevance
“…A recent study suggested that prolonged viewing of video lectures or attending real-time video class meetings may lead to Internet cognitive fatigue that affect learning effectiveness. Moreover, distraction and reduced focus due to independent learning and recurring problems of Internet usage and network may affect student online learning performance (Shao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that prolonged viewing of video lectures or attending real-time video class meetings may lead to Internet cognitive fatigue that affect learning effectiveness. Moreover, distraction and reduced focus due to independent learning and recurring problems of Internet usage and network may affect student online learning performance (Shao et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The utilization of social media and mobile devices in higher education is a recently emerged occurrence that has not been well studied (Ansari & Khan, 2020). Individual motivation is closely linked to the effectiveness of learning, whether it is formal or informal, as self-directed learning serves as the foundation for all types of learning (Shao et al, 2022). Digital technologies have an impact on perceived learning (Alexiou et al, 2022).…”
Section: Insignificantmentioning
confidence: 99%
“…Online learning is one such method, allowing for convenient learning without time and space constraints. It can be regarded as a technique that facilitates self-directed learning by permitting repeated learning based on the learner's proficiency level [51]. Although this study was conducted prior to COVID-19, online learning remains active post-COVID-19, with increasing demand owing to limitations in the clinical environment [51,52].…”
Section: Effectiveness Of the Nursing Practice Education Using M-lear...mentioning
confidence: 99%